Individual load–velocity measures are associated with 2,000-m rowing ergometer performance in German national rowers - Jacobs, Mats Willem; Schumann, Moritz (Frontiers in Sports and Active Living, 2025)
ObjectiveNeuromuscular abilities were previously linked to 2,000 m rowing performance (TT) but the relationship with load-velocity profiles [LVP; e.g., peak power (PP) and power at different relative loads] remains unclear. This cross-sectional study assessed the associations between these parameters and TT and different race splits in well-trained rowers.MethodsWe included 63 male (age: 18.5 ± 3.3 years) and 50 female (age: 19.3 ± 3.5 years) rowers. Within 2 weeks, 1 repetition maximum (RM), PP and power at 30% to 90% 1RM in the squat, deadlift and bench-pull were assessed by LVP and TT was performed on a Concept2 ergometer. Associations between neuromuscular parameters and TT were analyzed using generalized linear models.ResultsAssociations with TT were found for 1 RM in squat, deadlift and bench-pull (β: −32.64 to −95.15; all p ≤ 0.050), PP of deadlift and bench-pull (β: −21.79 to −71.78; p ≤ 0.020) but not PP of squat (p > 0.050). Power at 30% and 50% in squat, 30%, 50% and 70% in deadlift, and 30%, 50%, 70% and 90% in bench-pull of the respective 1 RM correlated with TT (β: −10.78 to −51.57; p < 0.050). 1 RM and PP of deadlift and bench-pull were associated with all four race splits (p ≤ 0.037), while PP of squat was linked only to the first 500 m (p < 0.030).ConclusionWhile deadlift and bench-pull power appeared to be good predictors of TT, the squat power might affect TT only at low loads (i.e., 30% and 50%) and the first part of the race. These findings underline the overlooked importance of high movement velocities for rowing performance.